IPEX as a Result of Mutations in FOXP3 - Hans J. J. van der Vliet; Edward E. Nieuwenhuis (Clinical and Developmental Immunology)
Immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare disorder caused by mutations in the FOXP3 gene that result in the defective development of CD4+CD25+ regulatory T cells which constitute an important T cell subset involved in immune homeostasis and protection against autoimmunity. Their deficiency is the hallmark of IPEX and leads to severe autoimmune phenomena including autoimmune enteropathy, dermatitis, thyroiditis, and type 1 diabetes, frequently resulting in death within the first 2 years of life. Apart from its clinical implications, IPEX illustrates the importance of immunoregulatory cells such as CD4+CD25+ regulatory T cells.